Potential Risk Factors for Ventriculoperitoneal Shunt Implantation in Paediatric Patients with Posthemorrhagic Hydrocephalus of Prematurity Treated with Subcutaneous Reservoir: An Institutional Experience - Bębenek, Adam K.; Kwiatkowski, Stanisław; Milczarek, Olga (Neuropediatrics, 2021)
Background Posthemorrhagic hydrocephalus of prematurity (PHHP) is a result of intraventricular hemorrhage (IVH). IVH occurs in 6 to 23% of the preterms in countries with advanced medical health care. Most of these patients will eventually require the use of ventriculoperitoneal shunt (VPS). The purpose of this study is to assess the risk factors of VPS implantation in patients with PHHP who have been treated with ventricular catheter with subcutaneous reservoir (VCSR).Methods The retrospective study was conducted evaluating 35 premature patients who suffered from severe IVH. Their mean gestational age was 28 weeks. The assessment included antenatal factors such as gestational age, birth weight, and intrauterine and perinatal infection. Postparturient period factors such as the IVH grade, time between diagnosis, and VCSR implantation and body weight on VCSR implantation were also considered in the study. Postprocedural complications, such as bacterial cerebrospinal fluid (CSF) infection, sepsis, and skin lesions, were evaluated. Data were calculated with R program, version 4.04.Results From among 35 evaluated patients, 23 (65.71%) required a VPS. Median of birth weight was 1,190 g. Infections were observed in 11 (31.43%) cases. Mean time between IVH diagnosis and VCSR implantation was 2.6 weeks. Postprocedural complications occurred in 19 (54.29%) patients. None of the evaluated factors has proven its statistical significance (p > 0.05) for being a potential risk factor for VPS implantation.Conclusion External factors seem to not affect the necessity of VPS implantation in patients after the severe IVH. Ostensibly, there seems to be no difference between the grades III and the IV of Papile's IVH scale regarding VPS implantation necessity.
Keywords: IVH; posthemorrhagic; hydrocephalus; prematurity; PHHP